2014
DOI: 10.1371/journal.pone.0086225
|View full text |Cite
|
Sign up to set email alerts
|

Economic Support to Patients in HIV and TB Grants in Rounds 7 and 10 from the Global Fund to Fight AIDS, Tuberculosis and Malaria

Abstract: People with TB and/or HIV frequently experience severe economic barriers to health care, including out-of-pocket expenses related to diagnosis and treatment, as well as indirect costs due to loss of income. These barriers can both aggravate economic hardship and prevent or delay diagnosis, treatment and successful outcome, leading to increased transmission, morbidity and mortality. WHO, UNAIDS and the ILO argue that economic support of various kinds is essential to enable vulnerable people to protect themselve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…These mainly related to lack of money to meet transport costs to the clinic and time and money lost during the long waiting hours at the clinic. These findings are similar to other studies that have shown that people with HIV frequently experience severe economic barriers to health care, which can prevent or delay diagnosis and treatment outcome (Richter et al 2014). Transport is a known barrier for poor people to access HIV treatment and care (Mshana et al 2006;Rosen et al 2007;Tuller et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…These mainly related to lack of money to meet transport costs to the clinic and time and money lost during the long waiting hours at the clinic. These findings are similar to other studies that have shown that people with HIV frequently experience severe economic barriers to health care, which can prevent or delay diagnosis and treatment outcome (Richter et al 2014). Transport is a known barrier for poor people to access HIV treatment and care (Mshana et al 2006;Rosen et al 2007;Tuller et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Economic incentives to improve medication adherence and clinic appointment fidelity, such as providing direct payments or nutritional supplementation to patients, have shown modest benefit. 41,42 Efforts to target historically stigmatized populations, which often faced the highest rates of infection and mortality, attempted to reduce reservoirs for HIV. 43 Though these strategies may not be evenly applied to a NCD model, addressing SDH may similarly prove to be both successful and cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…The running of dynamic is determined by the activation of shared principles, shared motivation, and capacity to take joint action. Collaborative dynamics is a cycle containing components affecting the process of collaboration (Hanefeld, 2014;Richter et al, 2014;Bridge et al, 2016).…”
Section: Discussionmentioning
confidence: 99%